The Urgency of Cyber Resilience in the Governance of Digital Libraries in Indonesia - Dwi Fajar Saputra (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid digital transformation of libraries in Indonesia has expanded access to knowledge but also exposed institutions to escalating cybersecurity threats. Specific Background: Increasing ransomware attacks, data breaches, and phishing incidents targeting educational institutions underscore the fragility of current library information systems. Knowledge Gap: Conventional cybersecurity measures often fail to ensure service continuity during cyber incidents, leaving a gap in sustainable protection strategies for digital library infrastructure. Aims: This study examines national data from Indonesia’s Badan Siber dan Sandi Negara (BSSN), evaluates TLS/SSL adoption in institutional repositories, and analyzes the British Library ransomware incident to identify systemic vulnerabilities. Results: Findings reveal insufficient encryption practices, fragmented incident response, and limited cross-institutional coordination. Novelty: The research advances a holistic cyber resilience framework—integrating flexibility, redundancy, diversity, and connectivity—and positions hybrid cloud infrastructure as a foundational enabler, complemented by international collaboration for knowledge sharing and collective defense. Implications: The study emphasizes the strategic role of the National Library of Indonesia in orchestrating global partnerships and aligning domestic cybersecurity policies with international standards, fostering sustainable governance and resilient digital library ecosystems. Highlights: Highlights vulnerabilities in Indonesia’s digital library infrastructure. Proposes a holistic cyber resilience framework with hybrid cloud adoption. Emphasizes global collaboration led by the National Library of Indonesia. Keywords: Cyber Resilience, Digital Libraries, Cybersecurity, Hybrid Cloud